Theoretical And Practical Considerations On The Valuation Of Revenue From Contracts With Customers Under IFRS 15 - Svetlana MIHAILA; Veronica GROSU; Mihaela - Ionela STANCIUC (SOCOLIUC); Violeta CODREAN (Communications of International Proceedings, 2023)
The dynamism and the extent of the evolution of economic and social life have led to the development of society as a whole and the progress of economic structures. In these circumstances, the needs of users of financial and accounting information are becoming more and more extensive, so that entities are obliged to adapt their information to market requirements. This paper aims to highlight the main theoretical and practical issues arising from the adoption and application of IFRS 15 'Revenue from Contracts with Customers' by companies. In order to achieve the purpose of the research, research methods specific to socio-human sciences have been used, such as analytical method, bibliometric analysis, comparison method, synthesis method, systemic method, induction method and logical deduction.  The results of the study demonstrate that the correct application of IFRS 15 is essential to ensure the proper functioning of the entity and accounting, which ensures a true and objective view of financial and accounting information and its comparability.
Keywords: IFRS 15; customer contracts; revenue recognition